Determinan Adversity Quotient dan Kemampuan Berpikir Kritis Dengan Stres Pada Mahasiswa Yang Sudah Bekerja - Riris Andriati; Fenita Purnama Sari Indah; Renti Yunita (STIKes Kharisma Persada, 2020)
The incidence of stress was quite high, reaching more than 350 million people in the world and ranked 4th in the world. The purpose of this study was to determine the relationship between adversity quotient and critical thinking ability with stress on nursing students in the Widya Dharma Husada Tangerang School of Health Science who are already working. The method of this research was analytic study with a cross sectional approach. The number of samples was 96 students at Widya Dharma Husada Tangerang School of Health Science in 2020. Sampling used non-probability sampling techniques with purposive sampling. The results showed that respondents had a moderate adversity quotient of 48 respondents (50%) and respondents who think critically are not good as many as 61 respondents (63,5%). Statistical test results obtained the, then it can be concluded that there is a significant relationship between adversity quotient with stress (p-value = 0.004) and critical thinking skills with stress (p-value = 0.015)